Multicentre study of perfusion magnetic resonance imaging in paediatric brain tumours. (12th October 2019) - Withey, Stephanie; MacPherson, Lesley; Oates, Adam; Powell, Stephen; Novak, Jan; Abernethy, Laurence; Pizer, Barry; Grundy, Richard; Bailey, Simon; Mitra, Dipayan; Arvanitis, Theodoros; Auer, Dorothee; et al.
Abstract: Studies in adults have shown that brain tumour perfusion correlates with grade. These studies are dominated by gliomas grade II to IV which are rare in children. The standard method, Dynamic Susceptibility Contrast MRI, provides estimates of relative cerebral blood volume (rCBV) but contrast agent leakage affects rCBV accuracy. The majority of perfusion studies have been conducted at single centres and variation in acquisition protocols makes the generalizability of results questionable. The aim of this study was to compare leakage-corrected rCBV with grade in paediatric brain tumours at multiple centres. Scans were analysed from 85 patients at 4 centres on 6 scanners prior to treatment. MRI protocols varied between centres. Histological diagnoses including grade were obtained. Whole-tumour median rCBV was significantly higher in the 45 high grade than the 40 low grade tumours (2.54 ± 1.63 ml/100ml vs 1.68 ± 1.36 ml/100ml, p=0.010). Low grade tumours, particularly pilocytic astrocytomas (grade I), displayed more contrast agent leakage consistent with their appearance on contrast enhanced images and required more leakage correction than high grade tumours. This finding differs from that in adults where contrast agent uptake is usually associated with higher grade. A cut-off of 1.70 ml/100ml for rCBV gave sensitivity and specificity of 76% and 65% respectively for discriminating grade. In summary, perfusion MRI can be used to help distinguish between low and high grade paediatric brain tumours. This finding is robust across multiple centres and acquisition protocols but correction should be made for leakage of contrast agent from the vessels.